Allah : for Muslims only? - Mohd Alami Musa (2014)
The Malaysian Court of Appeal’s decision to forbid the use of the term ‘Allah’ in the Catholic weekly The Herald is seen by many as a triumph for Muslims. The reference to the term ‘Allah’ is not exclusive to Muslims. In the context of Singapore, the court process is not necessarily the best means to resolve conflicts involving religion.